2004
DOI: 10.1111/j.1945-5100.2004.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and origin of amoeboid olivine aggregates in CR chondrites

Abstract: Abstract-Amoeboid olivine aggregates (AOAs) are irregularly shaped, fine-grained aggregates of olivine and Ca, Al-rich minerals and are important primitive components of CR chondrites. The AOAs in CR chondrites contain FeNi metal, and some AOAs contain Mn-rich forsterite with up to 0.7 MnO and Mn:Fe ratios greater than one. Additionally, AOAs in the CR chondrites do not contain secondary phases (nepheline and fayalitic olivine) that are found in AOAs in some CV chondrites. The AOAs in CR chondrites record a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 32 publications
10
91
0
Order By: Relevance
“…The mineralogy, petrology, 16 O-rich compositions, depletion in moderately volatile elements, such as manganese, chromium, and sodium, and the general absence of low-calcium pyroxenes associated with AOAs strongly suggest that AOAs are aggregates of grains of forsterite, aluminum-diopside, spinel, anorthite, and Fe,Ni metal that condensed in the nebula from an 16 Orich gaseous reservoir and aggregated with CAIs that formed earlier (Krot et al, 2004a(Krot et al, ,b, 2005dRuzicka et al, 2012a;Sugiura et al, 2009;Weisberg et al, 2004). Mineralogical and chemical similarities between AOAs and forsterite-rich accretionary rims suggest that AOAs formed contemporaneously with these rims.…”
Section: Origin Of Aoasmentioning
confidence: 96%
“…The mineralogy, petrology, 16 O-rich compositions, depletion in moderately volatile elements, such as manganese, chromium, and sodium, and the general absence of low-calcium pyroxenes associated with AOAs strongly suggest that AOAs are aggregates of grains of forsterite, aluminum-diopside, spinel, anorthite, and Fe,Ni metal that condensed in the nebula from an 16 Orich gaseous reservoir and aggregated with CAIs that formed earlier (Krot et al, 2004a(Krot et al, ,b, 2005dRuzicka et al, 2012a;Sugiura et al, 2009;Weisberg et al, 2004). Mineralogical and chemical similarities between AOAs and forsterite-rich accretionary rims suggest that AOAs formed contemporaneously with these rims.…”
Section: Origin Of Aoasmentioning
confidence: 96%
“…However, studies have shown that some, such as type B and C CAIs (Stolper, 1982;Wark and Lovering, 1982;Beckett and Grossman, 1988), or the compact type A CAIs (e.g., Simon et al, 1999) have probably crystallized from molten objects and could have also underwent a complex series of events including evaporation (Grossman et al, , 2002Richter et al, 2002) or partial melting (MacPherson and Davis, 1993). The complex history of other CAIs, such as fluffly type A inclusions (e.g., MacPherson and Grossman, 1984), spinel rich objects (MacPherson et al, 1983;Fegley and Post, 1985;Kornacki and Wood, 1985;McGuire and Hashimoto, 1989;MacPherson and Davis, 1994;Lin and Kimura, 2003;Krot et al, 2004a) or amoeboid olivine aggregates (Grossman and Steele, 1976;Komatsu et al, 2001;Krot et al, 2004b;Weisberg et al, 2004) is still not well understood (MacPherson et al, 1988;MacPherson, 2004). Their texture (e.g., fluffy aggregates of concentric objects for the spinel-rich inclusions) and irregular shape (e.g., amoeboid olivine aggregates) argue against crystallization from a liquid, with some inclusions such as most fine-grained spinel rich objects, showing a group II rare earth element pattern, interpreted as a condensation signature (Boynton, 1975;Kornacki and Wood, 1985;Sylvester et al, 1993).…”
Section: Nebular Condensatesmentioning
confidence: 97%
“…About one-fourth of these Mn-and Cr-rich olivines contain <1% FeO. Olivines with enrichments in these elements have been reported in carbonaceous chondrites, micrometeorites, and chondritic IDPs, though they are rare (Klöck et al 1989;Rietmeijer 1998;Gounelle et al 2002;Simon and Grossman 2003;Weisberg et al 2004). The wide Mg-Fe composition range of Wild 2 olivine is similar to that for anhydrous chondritic IDPs.…”
Section: Wild 2 Olivine and Low-calcium Pyroxenementioning
confidence: 99%